Faktor Penentu Perilaku Impulsive Buying Pada Fashion Business Di Kota Bandung - MH, Novia; Chaniago, Harmon (Jurnal Riset Bisnis dan Investasi, 2016)
Impulsive buying behavior is behavior that appears suddenly and without planned in advance by the consumer while shopping. Impulsive behavior arises because of the factors that encourage consumers to shop beyond the plan. From a business standpoint, this behavior will have a positive impact, by setting a good marketing strategy and understand the factors that cause this behavior it will be the manager of the business will get a large income. This study discusses the factors that lead to impulsive behavior by using descriptive analysis method. By using questionnaires distributed to a sample of consumers factory outlet with 100 respondents then processed using SPSS 16.0 will produce a mean as a reference level of each indicator. The factors that have been tested, the indicators store atmosphere has the highest mean value, which means that the store atmosphere factors which are elements of the store environment are a dominated factor that causes of impulsive buying. Expected benefits of this research can be perceived by various parties especially for business managers and readers as consumers, in order to be wise addressing the increasingly modern market developments from time to time.